EVALUATION OF COMPETENCY-BASED HISTORY LEARNING AT SMA NEGERI 2 MEDAN - Ginting, Merry Cinthia; Sumantri, Pulung; Aisyah, Sitti (Puteri Hijau : Jurnal Pendidikan Sejarah, 2025)
This study evaluates the application of competency-based history learning at SMA Negeri 2 Medan to assess its effectiveness, challenges, and impact on students. The research method used is a mixed approach that includes quantitative data from competency tests and questionnaires as well as qualitative data from interviews and observations. The test results showed variations in the achievement of students' competencies, with the highest achievement in understanding historical concepts and the lowest in analytical ability. The questionnaire revealed that most students and teachers consider competency- based methods to increase student engagement, despite obstacles such as difficulty connecting materials to daily life and technological limitations. Observations in the classroom highlight the effectiveness of methods such as group discussions and projects, but also point to the need for improved teacher training and technological facilities. The study concludes that while competency-based history learning has the potential to improve students' learning experience, existing challenges need to be addressed through additional training for teachers, technological improvements, and the preparation of more structured materials. Parent involvement and community support were also identified as important factors in the success of this learning.